(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cosmetic Gynecology practice has previously been labelled as purely esthetic and luxury based. This case report demonstrates that this novel practice is useful for promoting positive mental health and menstrual function. Case presentation: A 16-year-old nulliparous presented with esthetically displeasing results following genital surgery in childhood for a perineal mass with resultant posterior fourchette webbing. The esthetic result was noted to cause her mental distress and difficulty in tampon use. Correction of the untoward surgical effect allowed easy tampon use, prevented future dyspareunia, and improved her overall mental health. Discussion: Posterior fourchette webbing resulting from poor technique in labia minoraplasty leads to chronic perineal pain and dyspareunia. The resultant esthetics can also be displeasing. Surgical revision can alleviate these effects and improve self-esteem and mental health. Conclusion: Previously labeled as elective and occasionally unnecessary, cosmetic gynecology can improve menstrual and reproductive function as well as mental health in women of reproductive age and adolescents.